Does the media matter to suicide?: Examining the social dynamics surrounding media reporting on suicide in a suicide-prone community. (May 2017) - Mueller, Anna S.
Abstract: Despite the widespread acknowledgement by public health organizations that media reporting matters to suicide, this link has been much debated and the mechanisms undergirding it poorly understood. With this study, I combine a media analysis with ethnographic data collected during 2014–2016 (N = 91) to examine the social dynamics surrounding media reporting on suicide in a community (that I call Poplar Grove, USA) with an enduring adolescent suicide problem. I illustrate how the media crafted a particular story about why youth die by suicide that emphasized academic pressure over other plausible causes. In so doing, the media may have broadened ideas about when suicide is seen as an option. However, I also provide evidence that cautions against attributing too much causal power to the media. The media coverage in Poplar Grove reflected conditions that were already present in the community; it was already a high-pressure place for youth to live with widespread mental health stigma. These factors likely shaped media reporting, while also contributing independently to the suicide problem. Finally, I found that the suicide deaths that received media coverage were those that triggered significant cognitive dissonance and thus were much discussed among youth, independent of the media reporting. This generated ample opportunities for peer role modeling of suicide. Thus, while the media may have helped solidify a certain view of suicide in the community, it was not the only social force contributing to suicide in Poplar Grove. While the findings from this study do not negate the importance of responsible reporting on suicide, they do contextualize the role of the media in suicide and suggest that researchers must take a broader view of how suicide suggestion operates in the media and in social contexts. Highlights: Ethnographic and media data are used to examine the role of the media in suicide. Local media selectively features suicide motives that appeal to local audiences. Community factors, like mental health stigma, shape how the news reports on suicide. Deaths that receive media coverage are also highly discussed via other channels. Media reports on suicide are both products and producers of local culture.